CENTRAL ASIA’S HYDROPOWER PROBLEMS: REGIONAL STATES’ POLICY AND DEVELOPMENT PROSPECTS - BAKAS UULU, Bakhtiar; SMAGULOV, Kadyrzhan (CENTRAL ASIA AND THE CAUCASUS, 2011)
Water in Central Asia has always been not only a source of life, but also a source of disputes. This is because the region has been agricultural from time immemorial and rice and cotton, which require a lot of irrigating, are its main crops. But most of the region is extremely arid; water evaporation in Central Asia is higher than in similar regions of the world. This, in turn, is the reason for the insufficient drainage density. In the expanses of Central Asia’s desert lowlands, the drainage density amounts to 2 m per 1 sq. km, whereas the same index in the northern part of the Russian lowlands amounts to 300- 350 m per 1 sq. km. Another important feature of Central Asia is that the amount of precipitation and, consequently, the runoff perceptibly increases only in the highlands. So the main water resources are controlled by mountainous Kyrgyzstan and Tajikistan; these countries account for a total of 80.7% of the entire region’s runoff. Both republics use river water to generate electricity for export and for domestic consumption, while Kazakhstan and Uzbekistan use it only for irrigation purposes. In this scenario, Tajikistan and Kyrgyzstan increase water discharge in the cold winter months in order to engage the hydropower plants during increased electricity consumption and reduce it in the summer in order to replenish the amount of water in the reservoirs, again with the aim of engaging hydropower capacities during the winter. But this leads to waterlogging of Kazakh and Uzbek territory in the winter and a shortage of irrigation and drinking water in the summer. This strikes a hard blow at the economy: according to some experts, the Central Asian countries incur up to $770 million in economic losses from the submergence of farmland in the winter and water shortages in the summer.1In the former Soviet Union, attempts were made to resolve this problem by creating a Joint Energy System responsible for controlling and ensuring the rational use of river runoff, as well as for distributing electricity in a way that avoided grid overload. This goal was reached by means of energy exchange: Kazakhstan and Uzbekistan delivered gas, coal, and petroleum products to Kyrgyzstan and Tajikistan, while the latter, in turn, discharged water during the vegetation periods and supplied electricity. This streamlined energy exchange consolidated the countries. But when the Soviet Union collapsed and the economic ties broke down, the region’s countries were left to resolve their hydropower problems on their own.In 1998, the independent Central Asian countries tried to tackle the issue on the basis of a framework agreement among Kazakhstan, Uzbekistan, Kyrgyzstan, and Tajikistan on the joint and comprehensive use of the hydropower resources of the Naryn and Syr Darya reservoirs and the Toktogul hydro system.It should be noted that use of the shared water resources in Central Asia today is becoming a political rather than an economic issue. Common integration mechanisms are needed, the first of which should be an effective agreement on water and energy.2 In turn, integration will help to consolidate efforts to improve the socioeconomic situation in the region’s states, create a large integrated market of 50 million people, as well as free trade areas, raise the efficiency of mutual investments, and ensure coordinated foreign policy actions.This means that the CA countries are extremely interdependent on each other regarding water use issues. It should also be kept in mind that water shortage in the region will become even more acute in the future due to population growth, the development of industrial and agricultural production, and the increase in arable land.